A Heart Rate Calculation Method Based on Dynamic Rectangular Window Interception. Issue 2 (February 2019) - Lu, Yujia; Du, Ping; Xiong, Xiaotian; Qian, Lang; Ou, Jianrong; Zhang, Jinqu
Abstract: Aiming at the detection of instantaneous heart rate of heart sounds, a dynamic rectangle window interception calculation method was designed and a heart sound acquisition system was developed. The system can be used to monitor the state of heart at home for adults and foetuses. The algorithm can be used for analysis of adult heart sounds, fetal heart sounds acquired by the acquisition system and ultrasound Doppler heart sound. The algorithm firstly performs a normalization processing on the sound signal and then filters the filter, captures the data in a rectangular frame dynamically, locates the heart sound signal, calculates the instantaneous heart rate, and finally obtains the heart rate with high accuracy. Study shows that the heart rate algorithm has the characteristics of high recognition accuracy and fast calculation speed, which can realize the convenient and rapid home heart rate monitoring for adults and fetuses.